AN ANALYSIS OF FIGURATIVE LANGUAGE FOUND IN KICK ANDY TALKSHOW PROGRAM IN METRO TV - Maria Claudya; Sondang Manik; Rotua Elfrida (Jurnal Scientia, 2022)
The purpose of this study is to determine the types of figurative language and the most dominant types of figurative language used by speakers in kick Andy talkshow. The writers use theory by Keraf's (2010) to classify the figurative language used by speakers. This study uses a qualitative descriptive analysis method in analyzing the data. The data were obtained from conversational sentences, and statements in the Kick Andy talk show from television shows. The amount of data from this study were figurative language sentences show that it was found hyperbole 29 (25.89%), Irony/cynicism,sarcasm 19 (16.96%), personification 18 (16.71%), allegory 13 (11,60%), methapor 11 (9,82%), metonymy 6 (5.35%), satire 5 (4,46%), synecdoche 1 (0,89%). The most dominant type of figurative language is hyperbole, it can be seen that hyperbole intends to help express strong emotions, emphasize something, or even evoke humor for the listener and can increase the impression of influence.